PERANG PARADIGMA: DAPATKAH MENDAMAIKAN METODOLOGI PENDEKATANKUANTITATIF DAN KUALITATIF - Helmi Noviar; Ery Jayanti; Saiful Badli (JURNAL EKOMBIS, 2019)
The aim of this article is to describe how the paradigm qualitative and quantitative occur and its evolution concisely and the distinction between these two paradigm in the early days and particularly in the mid 1950’s which cause the paradigm wars on methodology and also epistemology point of view in the social science and economics dicipline. Both qualitative and quantitative significantly contribute in the social science overall. In addition to, the Nobel Prize winner in 1974Gunnar Myrdal inAsian Drama: An Inquiry Into the Poverty of Nations (1957) by using sociological frameworkand Garry S. Becker, winner of the 1992 economic Nobel in his doctoral dissertation Discrimination in the Market Place (1955) which included elements of crime, social conflicts (racial discrimination), and institutional economics in examining economic problems. The dichotomy of the qualitative and quantitative approaches is no longer relevant, because both have their advantages and disadvantages, in the qualitative approach the process of getting realistic data is quite good and comprehensive while in the quantitative approach provides a particularpicture or pictures of reality. Therefore, mixed method that can cover each other's shortcomings. Nevertheless, the process of obtaining truth is not just a methodological paradigm, but there is something called epistemological process so that the truth that is revealed as a science is describing an objective reality.Keywords: mixed method, qualitative and quantitative, triangulation